The Conversational Implicatures and Violations of Maxims In the Utterances of the Characters Sabdo and Intan Kuncoro in the Film Janur Ireng - Azein Sucahyono (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2026)
The film Janur Ireng contained conversational implicatures and maxim violations in the dialogue between the characters Sabdo and Intan, which were deliberately used to attract viewers to the story. This research aims to analyze the use of conversational implicatures and maxim violations in the utterances of the characters Sabdo and Intan Kuncoro to reveal the implied meaning behind the conflict. The approach used was a descriptive qualitative approach, using the Miles and Huberman interactive analysis model, which included data reduction, data presentation, and conclusion. Data in the form of characters' utterances that contained maxim violations were collected by listening to and taking notes on relevant dialogue in the film. The research results showed that all key utterances were special conversational implicatures whose meanings were highly dependent on the context of mystical revenge. Sabdo violated the maxims of relevance and manner through philosophical allusions as an instrument of intimidation and power, creating a mystical atmosphere. On the other hand, Intan violated the maxims of quantity and quality as a form of self-defense mechanism, a reflection of trauma, and a denial of the reality of the terror she experienced. This research concluded that the use of indirect language in this film set in Javanese culture was effective in building narrative tension while strengthening the portrayal of the characters as both perpetrators and victims of curses.